Dynamic material flow analysis of titanium sponge in China: 2000–2019. (15th October 2022) - Hu, Xinyi; Luo, Fanjie; Lin, Jing; Wang, Minxi; Li, Xin
Abstract: Titanium is vital to daily life and national security. And titanium sponge is the most important raw material in the production of titanium industry. Therefore, understanding the material cycle flow of titanium sponge in China can help to understand the future use of titanium at global and national levels. This paper traces titanium sponge flows, stocks, and loss in China using dynamic material flow analysis from a life cycle perspective from 2000 to 2019. Combined with the analysis of Shared Socioeconomic Pathways (SSPs) scenarios, we forecast potential changes characteristics of titanium sponge demand in the future. We find that firstly, due to the difficulty of critical technologies in the production of aviation-grade titanium sponge, more than 70% of high-quality titanium sponge is heavily dependent on imports. Secondly, many middle to low-end fields use titanium materials, and the social stock in the chemical industry is relatively large, accounting for 47%. As China's economic development rate increases, the demand for titanium sponge may increase by 150%–250% from 2020 to 2060. In addition, the demand for middle to high-end areas will be a crucial area in the future. Relevant policy measures should pay more attention to the production, processing, and recycling stages of titanium sponge to promote the healthy and sustainable development of titanium sponge in the future. Notably, the scenario results reveal key opportunities and demand trends for developing titanium sponge in the future. It is extremely important to the Chinese and global titanium industry. Highlights: Quantify the life-cycle flows of titanium sponge in China from 2000 to 2019. Demand for titanium sponge may increase by 150%–250% from 2020 to 2060 based on SSPs. The cumulative social stock of the chemical industry accounts for 47% from 2000 to 2019. The demand for mid-to-high-end areas will be a crucial area in the future. Ensuring the safety of titanium sponge supply is the focus of future policies.